Pesca artesanal sostenible en el municipio de Zambrano Bolivar (2019)
The present study was developed with the general objective of Analyzing the dimensions of sustainable artisanal fishing in the municipality of Zambrano – Bolívar. To achieve this goal, the research is based on the theoretical basis provided by the Food and Agriculture Organization of the United Nations [FAO] (2019) and Bertolotti (2016). Methodologically it is developed as a study with quantitative approach, descriptive scope and non-experimental field design where a questionnaire of 31 items was applied to a sample of 51 artisanal fishermen from the municipality of Zambrano-Bolívar. The results allowed identifying the current situation of artisanal fishing activity in the social, economic and environmental dimension of artisanal fishing activity; highlighting the low training of fishermen, the good practices they perform, the low income received and the low residue of their work. It is concluded that it is essential that the state is more concerned with fishing activity to promote it from efficiency and good practices.